2018
DOI: 10.1016/j.jhin.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and the importance of meeting the needs of healthcare workers: a qualitative study on Ebola

Abstract: The experiences of HCWs dealing with patients with suspected Ebola can direct improvements in generic preparedness for highly transmissible diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
112
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(130 citation statements)
references
References 17 publications
(12 reference statements)
0
112
1
2
Order By: Relevance
“…During this period, there are changes in the work process of these professionals, such as extra shifts, unpredictable working hours, performing tasks that do not belong to their daily routine, change of unit and team, besides the need for a reorganization of private and social life. Also the risk of exposure to highly infectious pathogens while working, these aspects can cause fear of contamination and be a source of infection for close contacts, such as family members (2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…During this period, there are changes in the work process of these professionals, such as extra shifts, unpredictable working hours, performing tasks that do not belong to their daily routine, change of unit and team, besides the need for a reorganization of private and social life. Also the risk of exposure to highly infectious pathogens while working, these aspects can cause fear of contamination and be a source of infection for close contacts, such as family members (2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…A study on Lassa Fever outbreak among Health care workers (HCWs) showed that none of the study participants met the minimum standards of infection prevention practices during the rst contact with fever cases (12). Infection prevention and control behaviors are in uenced by factors such as the occurrence of an epidemic, contact with con rmed and suspected cases, key clinical departments (such as intensive care unit and emergency department) that are critical risk factors in the pandemic outbreak and always cited as important causes of high healthcare-associated prevalence worldwide (13)(14)(15). years of experience and preparedness are other factors associated with healthcare workers' infection prevention and control behaviors (14).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the Lassa Fever outbreak among Health care workers (HCWs) showed that none of the study participants met the minimum standards of infection prevention practices during the rst contact with fever cases (12). Infection prevention and control behaviors are in uenced by factors such as the occurrence of an epidemic, contact with con rmed and suspected cases, key clinical departments (such as intensive care unit and emergency department) that are critical risk factors in the pandemic outbreak and always cited as important causes of high healthcare-associated prevalence worldwide (13)(14)(15). years of experience and preparedness are other factors associated with healthcare workers' infection prevention and control behaviors (14).…”
Section: Introductionmentioning
confidence: 99%